DESIGN ACTIVITY OF HIGH SCHOOL STUDENTS IN THE PROCESS OF TECHNOLOGICAL EDUCATION - Харитонова, Валентина (Modern engineering and innovative technologies, 2024)
The article highlights the role of design education in the process of technological training of high school students. The author emphasizes the importance of using design elements when involving students in project activities in technology classes. The fo